A Comparative Performance Study of Plasmon-induced Charge Separation of Au@TiO2, Au@Fe2O3, and Au@ZnO Photocell Thin-films (Journal of Scientific Research, 2013)
The gold colloidal nanoparticles was prepared by citrate reduction from chloroauric acid (HAuCl4·4H2O). An ITO glass was coated with nanoporous TiO2, Fe2O3 and ZnO by squeegee method. The squeezing coated films were loaded with Au-nanoparticles by depositing technique. The film was characterized by UV-visible transmittance absorption spectroscopy, SEM, XRD, XPS, and EDX techniques. The Pt counter electrode was prepared by a magnetron sputter method on an ITO glass. The semiconductor with Au-loaded film was used as a working electrode whereas Pt film was used as a counter electrode in a solar cell. The charge was separated by short circuit current and an open circuit voltage and the cell efficiency was measured by IPCE analyzer. The comparative photocurrent-performance of different semiconductors loaded with Au-nanoparticles was analysed. Au@TiO2, Au@Fe2O3, Au@ZnO were found to be suitable films for photo-current production having a good efficiency with Au@TiO2 as the best of the three.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.13391 J. Sci. Res. 5 (2), 245-254 (2013)